2006
DOI: 10.1111/j.1748-5827.2006.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the short‐term outcome following thoracic surgery in 98 dogs

Abstract: The short-term outcome following thoracic surgery is influenced by diagnosis. The thoracic approach is determined by intrathoracic disease, but may influence outcome by affecting the incidence of postoperative wound complications. The risk of thoracic drain complications increases with drain duration, which is influenced by the underlying disease. Drains should be maintained for the minimal amount of time possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 14 publications
0
59
0
Order By: Relevance
“…Dehiscence of the diaphragmatic closure (Baines 2016) and of the coeliotomy (de Rooster 2016) are usually caused by poor surgical technique. Complications associated with intercostal thoracotomy and median sternotomy are well known with the most common ones being wound-related (Tattersall and Welsh 2006, Liptak and others 2013, Tillson 2015, Moores 2016). Intercostal nerve damage, caused by rib retractors (Miyazaki and others 2011) or circumcostal sutures (Rooney and others 2004), plays a main role in postoperative pain after an intercostal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Dehiscence of the diaphragmatic closure (Baines 2016) and of the coeliotomy (de Rooster 2016) are usually caused by poor surgical technique. Complications associated with intercostal thoracotomy and median sternotomy are well known with the most common ones being wound-related (Tattersall and Welsh 2006, Liptak and others 2013, Tillson 2015, Moores 2016). Intercostal nerve damage, caused by rib retractors (Miyazaki and others 2011) or circumcostal sutures (Rooney and others 2004), plays a main role in postoperative pain after an intercostal approach.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports describing the incidence of TD complications in the veterinary literature (Bellenger and others 1996, Tattersall and Welsh 2006, Moores and others 2007. Of these, one paper evaluates TD complications in similar detail to this study (Moores and others 2007), and this paper describes a lower overall complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a point of controversy for some surgeons, as most retrospective studies have found thoracotomy tubes were placed in greater than 75% of thoracotomy patients. 2,3,30 We make the decision to place a thoracostomy tube based on the expectations of the tube. If there is a significant chance of continued accumulation of air or fluid after surgery, then a chest tube should be placed before recovery.…”
Section: Thoracostomy Tube Placementmentioning
confidence: 99%